Direct numerical simulation of compressible turbulence in acounter-flow channel configuration - Hamzehloo,A; Lusher,D; Laizet,S; Sandham,N (Physical Review Fluids, 2021)
Counter-flow configurations, whereby two streams of fluid are brought together from oppositedirections, are highly efficient mixers due to the high turbulence intensities that can be maintained.In this paper, a simplified version of the problem is introduced that is amenable to direct numericalsimulation. The resulting turbulent flow problem is confined between two walls, with one non-zeromean velocity component varying in the space direction normal to the wall, corresponding to asimple shear flow. Compared to conventional channel flows, the mean flow is inflectional and themaximum turbulence intensity relative to the maximum mean velocity is nearly an order of magnitude higher. The numerical requirements and turbulence properties of this configuration are firstdetermined. The Reynolds shear stress is required to vary linearly by the imposed forcing, witha peak at the channel centreline. A similar behaviour is observed for the streamwise Reynoldsstress, the budget of which shows an approximately uniform distribution of dissipation, with largecontributions from production, pressure-strain and turbulent diffusion. A viscous sublayer is obtained near the walls and with increasing Reynolds number small-scale streaks in the streamwisemomentum are observed, superimposed on the large-scale structures that buffet this region. Whenthe peak local mean Mach number reaches 0.55, turbulent Mach numbers of 0.6 are obtained,indicating that this flow configuration can be useful to study compressibility effects on turbulence.